Determination of the lifeline electricity tariff for Lesotho. (May 2020) - Mpholo, Moeketsi; Mothala, Matsoso; Mohasoa, Lebohang; Eager, Dan; Thamae, Retselisitsoe; Molapo, Tsita; Jardine, Tom
Abstract: Lesotho has a poverty rate above 50%, this renders a bulk of households connected to the grid unable to purchase enough energy to cover the essential basic needs at the current tariffs. This is supported by the declining average household consumption reported by Lesotho Electricity Company (LEC) despite an increasing customer base. Even more crucial, for low income countries, tariff levels should balance social stability, affordability, fairness, energy efficiency as well as cost recovery especially because the poor make up the majority of the population. Based on the poverty line, a lifeline tariff of 0.5 to 0.6 Maloti(M)/kWh (2017 tariffs) for a threshold of up to 30 kWh/month is proposed which is 35%–42% lower than the current domestic tariff of 1.424 M/kWh. The standard domestic tariff will need to increase to 1.856 M/kWh to allow for cross-subsidisation and hence maintain the financial standing of the utility company. The threshold capacity is based on the observation that in 2016, around 30% of grid connected households consumed less than 30 kWh/month which is enough electricity to cover the basic needs of an average household. Hence, an increasing block tariff (IBT) approach is proposed such that the first 30 kWh/month are set at a lifeline tariff and any excess is charged at a standard rate which is set such that it cross-subsidises the lifeline tariff. Highlights: Declining average household electricity consumption yet increasing customer base. A lifeline tariff for a threshold of up to 30 kWh/month is proposed. A lifeline tariff, 35%–42% lower than the current domestic tariff, proposed. Other tariffs to increase to allow for cross-subsidisation to maintain revenue. Currently 30% of grid-connected households consume less than the basic needs.